2010
DOI: 10.1186/1743-422x-7-178
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of alphasatellites associated with monopartite begomovirus/betasatellite complexes in Yunnan, China

Abstract: BackgroundAlphasatellites are single-stranded molecules that are associated with monopartite begomovirus/betasatellite complexes.ResultsAlphasatellites were identified in begomovirus-infected plant samples in Yunnan, China. All samples that contained alphasatellites also contained betasatellites, but only some samples that contained betasatellites contained alphasatellites. Thirty-three alphasatellites were sequenced, and they ranged from 1360 to 1376 nucleotides. All alphasatellites contain 3 conserved featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 30 publications
(38 reference statements)
1
45
0
Order By: Relevance
“…Amino acid sequence identity; the highest sequence identities are shown in bold replicate autonomously, and may have originated from nanoviruses, as they encode a nanovirus-like replication associated protein (Rep)[24][25][26]. However, the role of alphasatellites in the etiology of begomovirus-induced diseases is not well understood.…”
mentioning
confidence: 97%
“…Amino acid sequence identity; the highest sequence identities are shown in bold replicate autonomously, and may have originated from nanoviruses, as they encode a nanovirus-like replication associated protein (Rep)[24][25][26]. However, the role of alphasatellites in the etiology of begomovirus-induced diseases is not well understood.…”
mentioning
confidence: 97%
“…1c; Kon et al, 2007;Lee et al, 2011;Reddy et al, 2005;Seal et al, 2006a;Xie et al, 2010;Zhou et al, 2003). However, none has yet been reported from the NW .…”
Section: Satellites Associated With Begomovirusesesmentioning
confidence: 99%
“…1350 nucleotides) ssDNA molecule (termed alphasatellites, formerly DNA1) is usually found in association with OW begomovirus-betasatellite complexes (Mansoor et al, 1999(Mansoor et al, , 2000aNawazul-Rehman and Fauquet, 2009;Saunders and Stanley, 1999) but very recently, it has also been investigated to be associated with few NW begomovirus (Paprotka et al, 2010;Romay et al, 2010). In an extensive survey, Xie et al (2010) found that all samples those contain alphasatellites also contain betasatellites, but only few samples that contain betasatellites contain alphasatellites. In some cases, alphasatellites have been found to suppress viral symptoms (Nawaz-ul-Rehman and Fauquet, 2009).…”
Section: Satellites Associated With Begomovirusesesmentioning
confidence: 99%
“…It is interesting to note that most geminivirus-associated alphasatellites described from the Old World have been associated with monopartite begomoviruses infections that frequently include the presence of betasatellites [39,52,56]. In the New World where monopartite begomoviruses are very rare, betasatellites have not been identified and alphasatellites have only ever been reported to occur in association with bipartite Begomovirus infections [10,32,37].…”
Section: Introductionmentioning
confidence: 99%